A splitting iterative method for solving the neutron transport equation - Awono, Onana; Tagoudjeu, Jacques (Mathematical Modelling and Analysis, 2009)
This paper presents an iterative method based on a self‐adjoint and m‐accretive splitting for the numerical treatment of the steady state neutron transport equation. Theoretical analysis shows that this method converges unconditionally to the unique solution of the transport equation. The convergence of the method is numerically illustrated and compared with the standard Source Iteration method and multigrid method on sample problems in slab geometry and in two dimensional space.First published online: 14 Oct 2010